From Vedic Rite to Javanese Power: The Rājasūya as Political Allegory in the Sabhāparwa Merapi–Merbabu Manuscript Tradition - Galang Adhi Pradipta; I Made Suparta; Rindu Parulian Simanjuntak (Center for Research and Development of Religious Literature and Heritage, 2025)
This study examines how the Rājasūyarambha section of the Sabhāparwa Merapi–Merbabu (SP MM) manuscript reconfigures the Indian Rājasūya consecration rite into a political allegory for Javanese royal legitimation. Although previous scholarship has addressed the Vedic origins of the Rājasūya or its later cultural reception, the specific textual mechanisms through which the Old Javanese parwa tradition transforms this ritual into a model of political authority remain insufficiently explored. This research fills that gap by analyzing how the SP MM adapts ritual structure, narrative sequencing, and symbolic motifs to articulate a distinctly Javanese conception of kingship. The study employed qualitative descriptive analysis based on primary manuscript data from three SP MM witnesses (lontar and paper codices). Data were examined through comparative textual analysis, juxtaposing Javanese narrative elements with Vedic ritual sources and Javanese inscriptional terminology. The findings reveal three key mechanisms of allegorization: (1) the transformation of ritual violence into a metaphor for military conquest and territorial unification; (2) the elevation of spiritual recognition as a source of charismatic authority; and (3) the consolidation of social hierarchy through the cakravartin ideal. These mechanisms demonstrate how the SP MM functions as an ideological blueprint that shaped Javanese political thought. The study concludes that the SP MM not only legitimized rulers in its original context but also evolved into a repository of political memory, influencing later Javanese courts and sustaining long-term models of authority.